Sale & Purchase of Land Under Hand With Testimony Sign by Village Head or Customary Head - Yayuk Nur Hikmah; Gunarto Gunarto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
Land has a very important relationship and meaning for human life. Land is an immovable object or a fixed object whose ownership is regulated by the prevailing laws and regulations in Indonesia. Including the transfer of land rights due to buying and selling, the transfer of land from the seller to the buyer must use a valid or authentic proof of transfer made by the official making the land deed. In accordance with the laws and regulations. This study uses sociological juridical research methods, descriptive research specifications, aims to describe a problem in a certain area or at a certain time. This study uses secondary data sources which are divided into primary law, secondary law and tertiary law. The research results that have been collected are then analyzed qualitatively. The formulation of the problem was analyzed using the theory of legal certainty, the theory of usefulness or legal expediency, and the theory of legal justice. Based on the results of the study, it can be concluded, buying and selling land under the hands is still often done because people are not aware of the law of buying and selling land and the importance of proof of the transfer of land rights. The process of implementing the sale and purchase of land in the presence of the Village Head or Customary Head in Seruyan Regency is the parties coming to the village head's office and requesting a transfer of sale and purchase letter or proof of transfer of land rights to the village head and bring the conditions determined by the Village Head. The solution so that land registration can be carried out is that the process of buying and selling land must be carried out again in the presence of PPAT.